Unveiling a bimetallic FeCo-coupled MoS2 composite for enhanced energy storage. Issue 19 (13th March 2020) - Wang, Chengyang; Yang, Qidi; Qin, Guohui; Xiao, Yaoyao; Duan, Jingying
Abstract : Sodium and potassium-ion batteries are promising for energy storage owing to their source abundance and low cost; however, most active materials still suffer from sluggish kinetics, huge volume variations, and poor conductivity and cycle stability. Abstract : Sodium and potassium-ion batteries are promising for energy storage owing to their source abundance and low cost; however, most active materials still suffer from sluggish kinetics, huge volume variations, and poor conductivity and cycle stability. It remains a great challenge to explore appropriate electrode materials for scaled practical applications. Herein, mesoporous FeCo-incorporated MoS2 nanosheets encapsulated into a porous carbon framework (FeCo@C@MoS2 ) are smartly designed, artistically fabricated and evaluated for sodium and potassium storage. The FeCo@C@MoS2 electrode displays high reversible capacities of 380 mA h g −1 and 147 mA h g −1 at 500 mA g −1 for sodium and potassium storage, respectively. FeCo derived from a Prussian blue analogue promotes fast reaction kinetics of Na + /K + transport, introduces the formation of a stable solid electrolyte interphase layer (SEI) in both the interior and exterior of the cube-like porous nanostructure and controls the Na + /K + fluxes, suppressing the growth of metal dendrites. The porous carbon framework with large interstitial voids can effectively buffer volume variations and mitigate mechanical stress, contributing significantly to alleviate strain intensification on the surface layer between MoS2 and FeCo during repeated plating/stripping processes. Density functional theoretical calculations (DFT) further confirm that the synthesized nanostructure shows an intensified electron state, elevated anti-stress ability, high-quality SEI film and preferable Na + /K + adsorption energies. This in-depth investigation of the electrochemical performance and the extended energy storage mechanism based on metal alloy/sulfide nanostructures for sodium and potassium storage provides guidance for the smart design of heterojunctions for remarkable energy storage.